Principles of research methodology: A guide for clinical investigators - Borer, Jeffrey S.; Supino, Phyllis G. (Springer New York, 2012)
Principles of Research Methodology: A Guide for Clinical Investigators is the definitive, comprehensive guide to understanding and performing clinical research. Designed for medical students, physicians, basic scientists involved in translational research, and other health professionals, this indispensable reference also addresses the unique challenges and demands of clinical research and offers clear guidance in becoming a more successful member of a medical research team and critical reader of the medical research literature. The book covers the entire research process, beginning with the conception of the research problem to publication of findings. Principles of Research Methodology: A Guide for Clinical Investigators comprehensively and concisely presents concepts in a manner that is relevant and engaging to read. The text combines theory and practical application to familiarize the reader with the logic of research design and hypothesis construction, the importance of research planning, the ethical basis of human subjects research, the basics of writing a clinical research protocol and scientific paper, the logic and techniques of data generation and management, and the fundamentals and implications of various sampling techniques and alternative statistical methodologies. Organized in thirteen easy to read chapters, the text emphasizes the importance of clearly-defined research questions and well-constructed hypothesis (reinforced throughout the various chapters) for informing methods and in guiding data interpretation. Written by prominent medical scientists and methodologists who have extensive personal experience in biomedical investigation and in teaching key aspects of research methodology to medical students, physicians and other health professionals, the authors expertly integrate theory with examples and employ language that is clear and useful for a general medical audience. A major contribution to the methodology literature, Principles of Research Methodology: A Guide for Clinical Investigators is an authoritative resource for all individuals who perform research, plan to perform it, or wish to understand it better.